Family support, self-efficacy and suicidal ideation at emerging adulthood: a mediation analysis - Olabimpe Ajoke Olatunji; Erhabor Sunday Idemudia; Babatola Dominic Olawa (International Journal of Adolescence and Youth, 2020)
There is a paucity of knowledge on the mechanism by which social support predicts suicidal ideation at emerging adulthood. The present study was aimed to examine the mediating role of self-efficacy in the relationship between social support and suicidal ideation in a sample of 251 emerging adults (116 females; mean age = 20.84, SD = 2.34). Data analyses were conducted using structural equation modelling. Results indicated that an increase in family support significantly predicts a decrease in suicidal ideation. However, friends and significant other supports were not predictive of suicidal ideation. The outcome of mediation analysis showed that self-efficacy partially mediated the association between family support and suicidal ideation. It was recommended that family support should persist through the period of emerging adulthood notwithstanding that this life stage is characterized by more independence in lifestyle. Such kind of support may bolster self-efficacy in overcoming life difficulties that may predispose vulnerability to suicidal ideation at emerging adulthood.